Miljömedicinsk bedömning av den fysiska miljön i förskolan - Problembakgrund och utvärdering av en metodstudie - Liedholm,Fredrik (2014)
Children are a particularly vulnerable group in society. It is therefore carried out national surveys on how their health is affected by their home and residential environment. Many children, however, spend a significant proportion of their waking hours in preschools and that environment has not been as closely monitored, neither locally nor nationally. Therefore Occupational and Environmental Medicine in Lund and Västra Götaland developed the method: "The physical environment in preschool - an environmental health assessment". The goal is to give local municipal authorities an overview of the outdoor and indoor environment in their preschools. Data for the assessment is collected through a web-based survey sent to all preschool directors or principals in the municipality. The method also includes a report template to simplify compilation and presentation of the results at group level. The purpose of this master's thesis was to provide a theoretical background to the problem areas that the method concerns and evaluate how well the method worked. The method was evaluated in six municipalities of varying size in southern Sweden. Web-based surveys, sent to respondents in preschools, officials and contact persons in participating municipalities, were used for evaluation. The results show that the method basically worked well. The survey was perceived as easy to access, it was quick to answer, and the majority of the questions were easy to understand. The results were considered useful for planning and prioritizing the municipal environment and health inspections and provided preschools a chance to reflect on their shortcomings. Some suggestions for improvements were noted. The internal loss was quite large on some questions, which affects the strength of the results. A common factor for questions with large internal loss was that they lacked the answer "do not know". Therefore this option should be added to all questions that don´t have it today. A number of respondents, both preschool principals and environmental health officers, lacked questions about temperature and allergy-inspection. These are important questions that should be included in the survey. Many respondents in the municipalities thought it was too time consuming to compile the survey data and write a report by using the report template sent to them. A possible solution here would be to create a more adaptable report template, and simplify result presentation through macros that generate tables and charts directly from the raw data. An important issue that needs to be further investigated is the future management of the methodology. A possible manager could be Swedish Association of Local Authorities and Regions (SKL). Reporting data to SKL would allow access to good statistics on preschools physical environment locally, regionally and nationally.